2016
DOI: 10.1179/2151090315y.0000000002
|View full text |Cite
|
Sign up to set email alerts
|

CBCT analysis of bony changes associated with temporomandibular disorders

Abstract: Cone-beam computerized tomography findings are significantly associated with the clinical diagnosis of TMD. Osteophytes and flattening of the condylar surface are common features of TMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 18 publications
2
36
0
7
Order By: Relevance
“… 21 22 TMDs have been associated with condylar position in the glenoid fossa, 23 as well as bony and morphological changes of the condyle. 24 Slavicek 25 indicated that the 3D position of the mandibular bone was affected by the contact relationship of the teeth, and that structural adaptation of the TMJ was related to the eruption and coupling of permanent teeth. Therefore, all patients with Class II subdivision malocclusion included in the current study had to meet one of the following inclusion criteria: over 18 years of age and the eruption of all permanent teeth, excluding the third molars.…”
Section: Discussionmentioning
confidence: 99%
“… 21 22 TMDs have been associated with condylar position in the glenoid fossa, 23 as well as bony and morphological changes of the condyle. 24 Slavicek 25 indicated that the 3D position of the mandibular bone was affected by the contact relationship of the teeth, and that structural adaptation of the TMJ was related to the eruption and coupling of permanent teeth. Therefore, all patients with Class II subdivision malocclusion included in the current study had to meet one of the following inclusion criteria: over 18 years of age and the eruption of all permanent teeth, excluding the third molars.…”
Section: Discussionmentioning
confidence: 99%
“…19 These conflicting findings may result from differences in imaging techniques, 19 the diagnostic criteria for osteoarthritis, 18,19 age groups, 19 or ethnic diversity. 18,19 In a recent study, Talaat et al 20 performed a CBCT analysis of the bony changes associated with temporomandibular disorders (TMD) and found that osteoarthritic joints had significantly more condylar irregularities, osteophytes, and condylar flattening than non-TMD joints. The different signs CBCT findings in TMJ osteoarthritis 5 21 Statistically significant correlations were found for only four out of 32 paired comparisons.…”
mentioning
confidence: 99%
“…The main disadvantage of CT, compared to other radiological methods, is the high cost and the radiation exposure. Being introduced in TMJ evaluation in 1990s, cone beam CT ( Figures 6 and 7 ) is widely available now and provides high-resolution multiplanar reconstruction of the TMJ [ 31 , 32 ]. The main advantage of cone beam CT, compared to CT, is the lower radiation dose to the patient [ 33 35 ].…”
Section: Temporomandibular Joint Imagingmentioning
confidence: 99%